Eksistensi Sekolah Budaya Luwu I La Galigo dalam Menjaga dan Mengembangkan Tradisi Masyarakat Luwu - Nurul Fitriah; Mr. Bustan (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to elaborate on the efforts of the Luwu I La Galigo cultural school in developing local culture. To find out the form of teaching at the Luwu I La Galigo cultural school in passing down local cultures. And to find out the response of the community in the Luwu I La Galigo cultural school which participates in maintaining Luwu cultural values. To know. To achieve this goal, qualitative research methods were used by means of observation, interviews and documentation. The data obtained is then analyzed and interpreted based on theory and relevant research results. The results of this research show that the Luwu I La Galigo cultural school is an educational institution where the school studies local cultures in the land of Luwu. With the presence of the Luwu I La Galigo cultural school, it can provide efforts to the Luwu community to become agents of cultural development and preservation of traditional values. The form of teaching carried out by the Luwu I La Galigo cultural school is very efficient because there are four forms of teaching provided, namely discussion material, practice, presentations and study visits. The people of Luwu who participate in maintaining and preserving the culture and traditions of their ancestors and the people of Luwu also participate in the presence of the Luwu I La Galigo cultural school.